‘Bahasa Rupa’ dalam Komik Perempuan Indonesia Tahun 2000 – 2010 - Alvanov - Zpalanzani (PANGGUNG, 2012)
ABSTRACT Indonesia’s girls’ comics introduced in early 2000, mainly developed by girl comic artists, in- tended for girls readers and heavily emphasized girls’ romance as story theme. Girls’ comic is one of pop culture media that creates a unique visual language system through construction of its visual storytelling structure. This is an explanatory research that applies visual storytelling structure anal- ysis in order to depict its visual narrative elements and structure in girls’ comics. This research will extract the uniqueness of girls’ comics’ visual storytelling structure and visual language system. As the result, girls’ comics are amplification of characters, emotional visual backgrounds, and emotional transition which marked by establishing shots as sequence margin in its visual storytelling structure and visual language system. Keywords: girls’ comics, structure analysis, visual storytelling, visual language.